A correlation between char emissivity and temperature. (15th November 2019) - Schiemann, Martin; Gronarz, Tim; Graeser, Philipp; Gorewoda, Jeanette; Kneer, Reinhold; Scherer, Viktor
Abstract: The radiative behaviour of coal and char particles is an important input parameter for simulations of coal combustion and gasification processes, as those typically feature elevated reactor temperatures. For consideration of radiative heat transfer, accurate knowledge of particle emissivity is a pre-requisite. Combining theoretical considerations and experimental data from literature, a temperature dependent relation for char emissivity is provided.